Risk factors of incisional hernia after laparoscopic colorectal surgery with periumbilical minilaparotomy incision: a propensity score matching analysis - Yoonhong Kim; Ki Hyun Kim; Kyung Won Seo; Seung Hun Lee; Gyung Mo Son (Journal of Minimally Invasive Surgery)
Purpose: Incisional hernia is one of the most common complications after abdominal surgery conducted through a midline incision. Considerable debate remains regarding the design, comorbidity, suture material, and method. We investigated the risk factors for incisional hernia after laparoscopic colorectal surgery in the presence of limited surgery-related factors. Methods : A retrospective study was designed with 541 patients who underwent laparoscopic colorectal surgery performed by a single operator from January 2015 to December 2017. Due to open conversions, other abdominal operations, or follow-up loss, only 445 patients were included in the study. After propensity score matching, 266 patients were included. The study was based on diagnosis of incisional hernia on computed tomography at 6 and 12 months postoperatively. Results : Of the 266 total patients, 133 underwent abdominal closure using PDS (Ethicon), while the remaining 133 underwent closure with Vicryl (Ethicon). Of these patients, nine were diagnosed with incisional hernia at the 12-month follow-up: six (4.5%) in the Vicryl group and three (2.3%) in the PDS group (p = 0.309). The incidence of incisional hernia was significantly increased in females (odds ratio [OR], 15.233; 95% confidence interval [CI], 1.905-121.799; p = 0.010), in patients with body mass index (BMI) of >25 kg/m2 (OR, 4.740; 95% CI, 1.424-15.546; p = 0.011), and in patients with liver disease (OR, 19.899; 95% CI, 1.614-245.376; p = 0.020). Conclusion : BMI of >25 kg/m2, female, and liver disease were significant risk factors for incisional hernia after elective laparoscopic colorectal surgery performed through a transumbilical minilaparotomy incision.